HUBUNGAN PENGETAHUAN SUAMI TENTANG METODE KONTRASEPSI MOP (METODE OPERASI PRIA) DENGAN SIKAP SUAMI DALAM BER KB WILAYAH KERJA PUSKESMAS SEI PANAS KOTA BATAM - Asriati Asriati; Prasida Yunita (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
Participation in family planning will contribute significantly of population growth and treatment of reproductive. Factors that cause low men in the KB-lack of knowledge, the husband's attitude about ignorance and practice and the understanding that KB affairs is a woman's business. The purpose of this study was to determine the relationship of husband knowledge about contraceptive methods MOP (male surgery method) with the attitude of the husband in the KB MOP work area Health Center Sei Heat Batam Year 2017. This research is an analytical descriptive with cross sectional Sampling using purposive sampling method. This study was conducted in May-June 2017 with the number of respondents as many as 99 people. Data analysis using Chi-Square technique.From the resear ch result, the majority of husbands with less knowledge are 43 people (43,4%) and majority of husbands have negative attitude that is 66 people (66,7%). From the statistical test results obtained p = 0,000 <0,05 then there is a relationship between the husband's knowledge about KB MOP with the attitude of the husband in the KB MOP. It is expected that Sei Panas Health Center to provide health education to the husbands, especially about KB MOP MOP contraception